The duality of attraction in the poetry of Badr Shaker Al-Sayyab (Journal of the College of Basic Education, 2023)
The German poet Goethe says in a speech to him: The Parnassus Mountain has many peaks.It means that the glorious poets are other peaks of the mountain of poetry. Perhaps Badr Shakir al-Sayyab was one of theThe poets who fulfilled this saying, as he is a great poet by the standards of his time, with a high degree ofThe diverse culture that he drew from multiple sources, Arab and foreign, and Al-Sayyab Ibn Mafhoum on the authority ofPoetry tends not to reflect the effect of its experience by reciting at length and surrendering to the repercussions instead of the economy.And the focus is in contrast to the nazek of the angels, who perform their experiment with as few words as possible.With gestures and suggestions, and exploded with connotations, as if Nazca had memorized well Baudelaire's saying: TheEmotion offends art if it surrenders to it excessively. His method can be considered in the composition of the poem.Al-Tawilah is the first teacher in his poetry, and the second teacher in his poetic experience.The performance, so that al-Sayyab appears as if he had sent his poetry carelessly, expresses it only to the extent of his suffering, and does notHe suffers only as much as he expresses, hiding that secret effort between four walls. eitherThe third milestone in his experience is the return to a fundamentalism that was intransigent only to the extent he feared for the language.Arabic to degenerate into the general methods or the daily journalistic colloquial methods, which are full ofaggression against the language and its grammar and even its morphology and formulas, he kept that linguistic strength in his poetryAnd good casting and the use of metaphors and similes, and pay special attention to presentations.Badr's great experience is based on contradictory binaries. There are two extremes in the world: the AbsoluteAnd reality, life and death, light and darkness, bliss and hell, good and evil, and these two forcesThe two opposites that attract man towards God and good, and the second towards Satan and evil is